(untitled) (Journal of Renal and Hepatic Disorders, 2020)
Leptospirosis is considered a zoonosis acquired predominantly from contaminated surfaces and water, more commonly in emerging countries with limited sanitary conditions. Leptospira in the host unleashes an immune response that explains the symptoms and clinical signs; once it reaches the kidney and liver tissue, it can manifest with alterations that lead to acute and chronic diseases in both organs. Weil’s syndrome is the best known clinical manifestation with jaundice and acute kidney injury that could lead to multiple organ failure and death. For its diagnosis, there are simplified scores such as the SPiRO score, the microbiological criteria by microscopy or serological tests; the treatment focuses on antibiotics and, if necessary, provides organic support until the infection is curtailed. The purpose of this review was to address the impact of Leptospira infection on the kidney and liver, the mechanisms of organ damage, the clinical presentation, and diagnosis and management of this disease.